2004
DOI: 10.1111/j.1651-2227.2004.tb02685.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin T levels and myocardial involvement in children with severe respiratory syncytial virus lung disease

Abstract: Myocardial involvement is common in infants with severe RSV lung disease without congenital heart disease. cTnT level elevation was associated with hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 24 publications
0
30
0
3
Order By: Relevance
“…Features of shock have first been described in seven infants in an observational study on 218 infants admitted to a children's hospital [3]. Elevated cardiac troponin levels were found in 35 to 54% of infants with RSV infection ventilated in PICUs [13,14]. Elevated cardiac troponin I levels have also been found in children with RSV infection not requiring mechanical ventilation [15].…”
Section: Resultsmentioning
confidence: 99%
“…Features of shock have first been described in seven infants in an observational study on 218 infants admitted to a children's hospital [3]. Elevated cardiac troponin levels were found in 35 to 54% of infants with RSV infection ventilated in PICUs [13,14]. Elevated cardiac troponin I levels have also been found in children with RSV infection not requiring mechanical ventilation [15].…”
Section: Resultsmentioning
confidence: 99%
“…7,8 Pada anak dengan pneumonia, jejas miokardium telah dilaporkan dengan penanda enzim creatinine kinase MB (CKMB) 9 dan pada anak dengan infeksi saluran nafas bawah yang disebabkan oleh Respiratory Syncytial Virus (RSV) dengan menggunakan cardiac troponin T (cTnT) sebagai penanda. 10 Pemeriksaan cTnT telah digunakan secara luas sebagai penanda yang sensitif dan spesifik untuk deteksi merusakan jaringan miokardium (kualitatif ) serta menggambarkan banyaknya jaringan yang mengalami kerusakan (kuantitatif ). 11,12 Penelitian ini bertujuan menganalisis hubungan kadar cTnT sebagai penanda jejas miokardium dengan derajat pneumonia.…”
Section: Hasilunclassified
“…Furthermore, increased susceptibility to recurrent allergic wheezing and asthma may result as a consequence of exposure to RSV infection early in life [5,9,10]. Clinical reports have also shown that RSV infection may cause extra-pulmonary effects at the neurological, endocrine, cardiac and hepatic level [11][12][13][14][15][16]. Although the causes leading to these extrapulmonary symptoms have remained elusive, it is possible that both direct organ infection by RSV and damaging inflammatory responses promoted by the virus at those tissues could contribute to the observed detrimental effects [17,18].…”
Section: Introductionmentioning
confidence: 96%